Diagnostic Assessment of Small Dam Performance Using a Hierarchical Composite Index: Limiting Indicators and Robustness Analysis in Semi-Arid Area - Sessito Vincentius Sapay; Pitojo Tri Juwono; M. Amar Sajali (Jurnal Penelitian Pendidikan IPA, 2026)
Small dams are strategic infrastructure in semi-arid areas such as Kupang, where performance sustainability is shaped by technical and institutional dimensions. This study analyzes the performance of three small dams, namely Oelanisa, Bisiti, and Oekolo, using a hierarchical composite index to identify limiting indicators and examine weighting robustness within the Performance Index Model of Small Dams (IKEK). A total of 37 indicators across physical, O&M, institutional, and service aspects were evaluated through weighted linear aggregation and six weighting scenarios. Using an inverse scoring convention (lower = better), IKEK values were 2.44 for Oelanisa (Moderate-2), 2.86 for Bisiti (Moderate-4), and 2.97 for Oekolo (Poor), indicating systemic deficiencies despite water availability reliability. The O&M aspect contributed 63.51–66.43% to the total index, a consequence of its structural weight (0.53) combined with poor O&M performance, reflecting governance weaknesses rather than model imbalance. Staff competence held the highest effective weight (β = 0.1549) and greatest marginal impact (∆IKEK = 0.465), the maximum index gain achievable at optimal condition. Robustness testing confirmed ranking stability, demonstrating performance differences are structurally determined by actual score distributions. These findings affirm that strengthening O&M capacity and institutional governance is the primary rehabilitation priority in semi-arid small dam systems.